Mediating Role of Customer Satisfaction in Sales Promotion, Brand Image, and Reviews Toward Skintific Loyalty - Wisaka Mustika; Elfrida Viesta Napitupulu (Jurnal Manajemen dan Kewirausahaan, 2025)
Competition in the beauty industry is rising with the digital transformation. This study examines Skintific product loyalty on Shopee, focusing on customer satisfaction as a mediator between promotions, brand image, product reviews, and loyalty among Generation Z. Marketplaces provide consumers with easier access to a wider range of products, making long-term loyalty crucial for stable growth. Generation Z often follows trends when making purchasing decisions. Questionnaires collected data from 240 Shopee buyers of Skintific. Results show customer satisfaction fully mediates the effects of promotions and partially mediates the impacts of brand image and reviews on loyalty. These findings can help businesses refine their marketing strategies to cater to Generation Z's online preferences.